Linear analysis of equations of process treatment metals - Donatas Švitra; Jolanta Janutėnienė (Lietuvos Matematikos Rinkinys)
Linear analysis of equations describing treatment process of metals by cutting iš presented. The analysis is based method on D-expansion method. There is choose a areas of asymptotically stability as well as areas describing harmful autooscillations arising during the treatment of metals by cutting is discussed.